Moths and Caterpillars 2021
DOI: 10.5772/intechopen.96438
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pheromone Application Technology for the Management of Codling Moth in High Altitude and Cold Arid Region of Ladakh

Abstract: The codling moth is a threat to the apple industries in India. Currently, no solutions are available for the management of codling moth in Ladakh. Therefore, all fresh fruits from Ladakh are still banned due to quarantine regulations. Jammu and Kashmir and Himachal Pradesh and Ladakh are the three main apple producing states of India, both in quality and quantity. The ban on all fresh fruits from Ladakh directly affects the economy of rural populations. These fruits are sold in all the local markets of Kargil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…1d) are about 10.2 mm long and have a wing span of 15 mm, dusty greyish brown in colour having coppery wings with dark copper-colored posterior forewing margins, however, the hind wings are pale brownish grey. Similarly, Hussain et al (2021) also reported that codling moth adults having grayish brown color, one inch in length, had coppery wings with a dark copper color at the tip region. The adult moths hold the wings back over their abdomen in a tent-like shape while in a resting position.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…1d) are about 10.2 mm long and have a wing span of 15 mm, dusty greyish brown in colour having coppery wings with dark copper-colored posterior forewing margins, however, the hind wings are pale brownish grey. Similarly, Hussain et al (2021) also reported that codling moth adults having grayish brown color, one inch in length, had coppery wings with a dark copper color at the tip region. The adult moths hold the wings back over their abdomen in a tent-like shape while in a resting position.…”
Section: Resultsmentioning
confidence: 81%
“…At the entry points, excreta was thrown out, which was produced by the boring larvae and form tunnels inside the pulp of fruit to reach the seed locules and feed on the whole seed. Codling moth larvae bore into the fruits, and feed on seeds and create exit holes by pushing waste material out (Hussain et al, 2021). After feeding, the full-grown last instar comes out of the fruit for pupation.…”
Section: Resultsmentioning
confidence: 99%